Penjatuhan Pidana Terhadap Pelaku Inses Disertai Pembunuhan Di Indonesia - Zakia Syarika Zulkifli; Yunan Prasetyo Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The complex issue of incest, which involves sexual relations between close family members, has caused a stir in society. In Indonesia, incest is regulated in various laws such as the Criminal Code as regulated in Articles 284, 285, 294 and 338 of the Criminal Code and Law Number 35 of 2014 concerning Child Protection. In the crime of incest, there are several causal factors such as psychological instability, social pressure and the inability to understand ethical boundaries in family relationships. This research uses normative juridical legal research, using a statutory approach and a case approach. The formulation of the problem in this research is what are the factors that cause cases of incest accompanied by murder in psychological, social and economic aspects as well as what is the review regarding criminal penalties for perpetrators of incest accompanied by murder in accordance with positive law in Indonesia. In Indonesia, incest is not only seen as an immoral act, but is also threatened with strict criminal penalties. However, delving into the root causes of incest and the judge's considerations in handing down a decision against the perpetrator is an important step in understanding the complexity of this issue